OPTIMAL CONTROL USING SUB-RIEMANNIAN GEOMETRY WITH APPLICATION TO ISOPERIMETRIC PROBLEM ON SPHERE - Noor Hasmi, Abrari
Sub-Riemannian Geometry is the natural geometry where optimal control problems belong to. In this thesis, we investigate the relation between optimal control and Sub-Riemannian Geometry. Then we implement the optimal control and Sub- Riemannian geometry approach to solve isoperimetric problem. The thesis present the problem formulation, geometric interpretation, and solution, with the optimal control and Sub-Riemannian Geometry approach.